The introduction of the national e-health record into community pharmacy practice: Pharmacists’ perceptions - Mooranian, Armin; Emmerton, Lynne; Hattingh, H. Laetitia (John Wiley & Sons Ltd, 2013)
Objective: Personally Controlled Electronic Health Records (PCEHRs) were introduced for Australian health consumers in July 2012. This study aimed to determine, in the months prior to the launch, community pharmacists’ perceptions about practical and professional aspects relating to integration of the PCEHR into pharmacy practice, with a view to informing practice guidelines and training. Methods: Semi-structured interviews with 25 pharmacy owners and/or managers from 24 community pharmacies in Perth, Western Australia, were undertaken during March–April 2012. Participants were given a standardised briefing about the PCEHR before exploratory questioning regarding the expected integration, benefits and challenges of the system in pharmacy practice. Key findings: Despite some awareness of the impending introduction of PCEHRs via the lay media, pharmacists were almost unanimously uninformed about the intended rollout, design and functionality of the system for health consumers and practitioners. Participants expressed concerns regarding patients’ control over their data management, time associated with staff training, technical upgrades and resource allocation. Obstacles included pharmacists’ inability to legitimately access patient data outside consultations. Pharmacists expected flexibility to record clinical activities and health services. Priorities identified for the profession were remuneration, medico-legal guidelines and boundaries, and clarification of roles and responsibilities.Conclusions: Despite being unaware of details surrounding integration of PCEHRs in practice, community pharmacists provided insights into their expectations and concerns and the perceived benefits relating to implementation of the system. Training priorities and practice guidelines should address ethical data management and optimal use of electronic health records for clinical services.